Działania promocyjne jako element budowania marki miasta – przegląd działań promocyjnych miasta Rzeszowa - Przepióra, Sabina (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
Nowadays cities as well as companies and all institutions competes for the best place on market. To do so they using territorial marketing. Thanks to it they could build, change and also keep image of the city. All this actions are using to build a strong and individual brand for all customers (in that case residents, tourists, investors and all outside viewers). What is important in territorial marketing is that all actions should be compatible with city character as well as its individual attributes and different then challengers actions in the same time. The main purpose of this article is description and analyze of all Rzeszow marketing actions. The article presents promotional activities, analyzes completed so far campaigns and indicates the main tourist products of the city, which include: inter alia underground route underground circular walkway and a multimedia fountain. It also shows that the city uses new forms of promotion and touring the place which is questing.
Keywords: city; Rzeszow; territorial marketing; promotion; image